The Effect of Contextual Teaching and Learning and Discovery Learning on Elementary Students' Mathematical Understanding - Desi Dwi Amelia; Sulis Janu Hartati; Kusmiyati; Windi Setiawan (LPPM STKIP Kusuma Negara, 2026)
For elementary school students, grasping mathematical principles is an essential skill required to apply the subject meaningfully. Yet, actual classroom instruction regularly concentrates on procedural mechanics rather than conceptual mastery. This quantitative, quasi-experimental research assessed the individual and combined effectiveness of Contextual Teaching and Learning (CTL) and Discovery Learning on pupils' mathematical grasp. The study was modeled around a single-group interrupted time-series approach, involving 17 sixth-graders from UPTD SD Negeri Ra'as, Indonesia. Evaluation metrics were derived from a validated, reliable test and computed using simple and multiple linear regressions within the IBM SPSS Statistics 25 environment. The investigation revealed that CTL significantly altered students' understanding (R2=0.949, p<.001), with Discovery Learning yielding a slightly higher magnitude of effect (R2=0.959, p<.001). Cojointly, the two teaching methodologies explained 99.1% of the fluctuations in the participants' mathematical comprehension (R2=0.991, p<.001). Ultimately, these insights imply that merging contextualized learning tasks with guided discovery serves as a highly effective pedagogical strategy to elevate conceptual math competencies at the primary level.